(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The paper explores the strategies for achieving sustained economic growth, focusing on manufacturing, innovation, and international trade. It highlights policy frameworks to overcome the middle-income trap and establish India as a global economic leader by 2047.